Literatur Review: Strategi Blended Learning dalam Meningkatkan Mutu Pembelajaran di Sekolah Menengah Atas (Studi Kasus pada SMA N 9 Binsus Manado) - Rotty, Viktory N. J.; Rambitan, Bella F.; Sumual, Syerri Y.; Sadsuitubun, Marisca A. B.; Wakur, Neiles (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this study is to find out how the Blended Learning strategy in improving the quality of learning at SMA N 9 Binsus Manado. This research uses the method of literature study. The results showed that the presence of the industrial revolution era 4.0 is a challenge for the field of education. Entering the era of the industrial revolution 4.0, educators (teachers) at all levels of formal education, including junior and senior high schools, are required to master the ability or expertise to adapt to new technology. This is intended to improve the quality of existing learning by utilizing growing technology. Blended Learning is one of the concepts of education 4.0 that can be used as a form of educator strategy in improving the quality of learning in the era of the industrial revolution 4.0, especially in fulfilling mastery of technology. Several blended learning models that have currently been implemented by SMA N Binsus Manado in order to improve the quality of learning include Google Classroom; Social Media Whatsapp, Facebook and Telegram; Moodle; Zoom Meeting; Edmodo and Microsoft Education Office 365.